Body image and social media sharing: a content analysis of public reactions to a body positive post on TikTok - Strach, Shannan (My University, 2023)
This study explored the public reactions of society to a post on TikTok created by Nessa May. In this video, Nessa May confidently shows her body, which does not fit the stereotypical beauty standards of society. She explains to viewers that it is okay not to fit beauty standards and to have a body type similar to her own. A content analysis of the 100 most recent comments reacting to Nessa May’s video identified five main themes including: love, thankfulness, emotions (happiness), beauty, and insecurities. The predominant theme seen was that of love towards Nessa May herself, as well as self-love and increased confidence in the commenters themselves (this made up 35% of all comments). Overall findings showed both support for the body-positive post, as well as an emphasis on the effect normative beauty standards have on women.
Keywords: body image; beauty standards; women; social media